1977
DOI: 10.1042/cs0520463
|View full text |Cite
|
Sign up to set email alerts
|

Porphyrins in Erythrocytes and Blood Plasma: Preliminary Studies with Qualitative Thin-Layer Chromatography

Abstract: 1. A simple chromatographic method for the study of porphyrins in erythrocytes and blood plasma, requiring little technician time, is described. The findings in adults and neonates are presented as well as those from severely ill patients. 2. The regular occurrence of uro-, copro- and proto-porphyrin in erythrocytes is deomonstrable as well as sporadic occurrence of tri-, penta-, hexa- and hepta-carboxylic porphyrin. The method gives, however, irregular values for protoporphyrin, which seems to occur in a more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…In Figure 3B, it is demonstrated that Ce 6 generates 1 O 2 very quickly, compared to Au NCs, however, the maximum amount of 1 O 2 is very similar to the amount which is generated by Au NCs after longer irradiation. Additionally, we observed that human plasma itself also generates 1 O 2 upon light exposure, which could be easily explained by the presence of endogenous photosensitizers, such as uroporphyrin, coproporphyrin, and protoporphyrin, in plasma [54]. Thus, our studies have demonstrated that Au NCs stabilized with plasma proteins can generate ROS under 405 nm light irradiation.…”
Section: Singlet Oxygen and Other Reactive Oxygen Species Generationsupporting
confidence: 50%
“…In Figure 3B, it is demonstrated that Ce 6 generates 1 O 2 very quickly, compared to Au NCs, however, the maximum amount of 1 O 2 is very similar to the amount which is generated by Au NCs after longer irradiation. Additionally, we observed that human plasma itself also generates 1 O 2 upon light exposure, which could be easily explained by the presence of endogenous photosensitizers, such as uroporphyrin, coproporphyrin, and protoporphyrin, in plasma [54]. Thus, our studies have demonstrated that Au NCs stabilized with plasma proteins can generate ROS under 405 nm light irradiation.…”
Section: Singlet Oxygen and Other Reactive Oxygen Species Generationsupporting
confidence: 50%